Komite Audit, Ukuran Perusahaan, Rasio Keuangan, dan Audit Lag - Vinella, Christina; Aminah, Aminah; Nilwan, Afrizal; Virgawenda, Tina Miniawati (E-Jurnal Akuntansi; Vol 34 No 2 (2024)DO - 10.24843/EJA.2024.v34.i02.p16, 2024)
The timeliness of submitting financial reports can be measured using audit report lag (ARL). Various studies observing the factors that influence ARL have shown opposite results so that this research is urgent to emphasize the results of previous research.This study aims to analyze the effect of liquidity, audit committee, leverage and company size on audit report lag in transportation and logistics companies on the IDX during the 2020-2022 period. The data used is secondary data through the results of annual financial reports. Thesample was selected through purposive sampling technique, only 23 companies met the qualifications. The analysis used is multiple linear regression through the SPSS version 25 program. The results of hypothesis testing show that liquidity and leverage have an impact on ARL. Meanwhile, the audit committee and company size have no impact on ARL. All independent variables simultaneously have an impact on audit report lag. The results of this study formulate that the OJK should review the deadline for presenting financial reports regarding monitoring companies registered with the IDX and protecting investors in the Indonesian capital market. Keywords:Audit Report Lag; Liquidity; Audit Committee; Leverage; Company Size